Farmers' adoptability of Mucuna fallowing and agroforestry technologies in the coastal savanna of Benin - Versteeg, M.; Amadji, F.; Eteka, A.; Gogan, A.; Koudokpon, V. (Elsevier, 1998)
As technologies to counter soil fertility decline, alley farming with Leucaena leucocephala and Gliricidia sepium, annual short-season Mucuna pruriëns var. Utilis fallowing, and perennial Acacia auriculiformis fallowing have been tested. With alley farming, timely pruning is a critical element in farmers' capacity to match on-station yield levels: 55% of the farmers who delayed pruning suffered about 60% yield losses. Farmers are now comparing a new alley band concept, grouping trees in bands 20 m apart with five times less tree/crop competition. However, an improved planted fallow of A. auriculiformis to regenerate exhausted soils grew a great deal in popularity because of quick regeneration of yields and a profitable bonus of good quality firewood. Mucuna, which was grown by 15 farmers in 1987 for Imperata control, is now known by almost 100 000 farmers. The regular use for soil fertility enhancement is, however, hampered by the lack of known uses for mucuna products. We developed recently a farmer-applicable detoxifying method for mucuna seeds, allowing incorporation of protein-rich mucuna flour into main staple dishes in Benin. We highlight the essential impact of farmer interaction on the course of experimentation, results and adoption.